PENGEMBANGAN MEDIA AUDIO VISUAL DALAM PEMBELAJARAN MENULIS KREATIF PUISI - -, Sofyan -; Wiryotinoyo, Mujiyono -; -, Sudaryono - (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2011)
This article is based on a developmental research which is aimed at constructing audio-visual media to assist poetry writing instruction. The media is developed by using the contextual approach. The Model Development employs the model of Alessi and Trollip’s (2001) which is emphasized on three main pillars of development: determining activity standards, project management, and ongoing evaluation. These three main pillars of model development then implemented in further three steps of planning, design, and development. Based on the data analysis of the development process, experts’ validation, and field trials of the product, it can be concluded that the quality of the audio visual media is good in assisting creative writing process. Therefore, it is suggested that the media can be used as a media in teaching creative poetry writing for senior high school students. Keywords: audio visual media, creative writing, poetry writing, teaching model development